PH-sauvagine from the skin secretion of Phyllomedusa hypochondrialis: A novel CRF-like peptide with smooth muscle contraction activity. (15th September 2015) - Zhou, Yu; Shaw, Chris; Chen, Tianbao
Abstract: Amphibian skin, and particularly that of south/Central American phyllomedusine frogs, is supposed to be "a huge factory and store house of a variety of active peptides". The 40 amino acid amphibian CRF-like peptide, sauvagine, is a prototype member of a unique family of these Phyllomedusa skin peptides. In this study, we describe for the first time the structure of a mature novel peptide from the skin secretion of the South American orange-legged leaf frog, Phyllomedusa hypochondrialis, which belongs to the amphibian CRF/sauvagine family. Partial amino acid sequence from the N-terminal was obtained by automated Edman degradation with the following structure: pGlu-GPPISIDLNMELLRNMIEI-. The biosynthetic precursor of this novel sauvagine peptide, consisted of 85 amino acid residues and was deduced from cDNA library constructed from the same skin secretion. Compared with the standard sauvagine from the frog, Phyllomedusa sauvagei, this novel peptide was found to exert similar contraction effects on isolated guinea-pig colon and rat urinary bladder smooth muscle preparations. Highlights: Identification of novel CRF-like peptide from skin secretion of Phyllomedusa hypochondrialis . Construction of cDNA library from the same skin secretion. Similar contraction effects found on isolated guinea-pig colon and rat urinary bladder smooth muscle preparations.